PTH-008 Endoscopy reporting in ulcerative colitis: identifying areas of suboptimal practice to define an intervention bundle. (June 2019) - Calderbank, Tom; Black, Grace; Theaker, Holly; Samaan, Mark; Tomkins, Oliver; Aslam, Maria; Caro, Simona Di; Rahman, Farooq; Mehta, Shameer; McCartney, Sara; Bloom, Stuart; Vega, Roser; et al.
Abstract : Introduction: The importance of endoscopic evaluation as part of the management of ulcerative colitis (UC) is becoming increasingly appreciated. However, the quality and completeness of UC endoscopy reports is variable. Previous studies have demonstrated that standardisation of reporting can optimise practice and there now exists expert consensus on which items should be included in a high quality UC endoscopy report. Our aim was to identify areas of suboptimal practice which could inform the design of an intervention bundle to improve reporting. We also aimed to identify any groups of endoscopists to whom the interventions should be specifically directed. Methods: Reports of 227 lower GI endoscopies (103 flexible sigmoidoscopies, 124 colonoscopies) performed on UC patients at UCLH between April-October 2018 were reviewed. Reports were evaluated against 10 endoscopic reporting items recommended by the Building Research in Inflammatory Bowel Disease Globally (BRIDGe) groups expert consensus exercise 1, as well as documentation of UCEIS scores. Thus, each report was given a mark out of 11. Subgroup analyses were carried using Mann-Whitney (continuous) or Fishers exact (categorical) tests. Results: The rate at which each reporting item was documented is shown in table 1 . Description of previous disease extent (3%), UC therapy (10%) and symptoms (9%) at the time of the procedure were all infrequently reported. However, perhaps the most clinically relevant finding was that an objective measure of disease activity was missing in nearly half of reports. Subgroup analysis demonstrated that non-consultants (trainees and nurse endoscopists) were significantly more likely to report UC therapies (p=0.045) and biopsy location (p=0.031). No other significant differences were observed for individual reporting items or overall score (median 5/11 in both groups, p=0.07). Conclusions: Our data demonstrates that many endoscopic UC reports are not consistent with optimal practice based on expert consensus. We identified areas that could potentially be optimised using an interventional bundle. Most importantly, the use of an endoscopic index. The interventional bundle should involve all endoscopists and could include such measures as local training sessions, hard-copy and online training materials, pooling of UC procedures on dedicated lists and integration of template reports into reporting software. Reference: Devlin SM, Melmed GY, Irving PM, et al. Recommendations for Quality Colonoscopy Reporting for Patients with Inflammatory Bowel Disease: Results from a RAND Appropriateness Panel. Inflamm Bowel Dis 2016;22:1418–24.